KELOMPOK KEPENTINGAN (INTEREST GROUP), KEKUASAAN DAN KEDUDUKANNYA DALAM SISTEM POLITIK - Mohammad Maiwan (Program Studi PPKn FIS UNJ & Asosiasi Profesi PPKn Indonesia, 2016)
The interest groups have a strategic position in society as a liaison between the community and government. Its presence to dynamic of political system. There are several types of interest groups, namely: Anomic groups; nonassosiasional; institutional; associational. The emergence of interest groups are going along with the rapid expansion of government's role in all areas of life. When expressing their interest to the government, interest groups use two ways: First, sell the issue to the political parties. Second, direct express their aspirations to the government. The method used is through; lobbying, mass media campaigns, as well as grass-roots pressure. The success to influence of the government depend on some aspects such as: Political culture, institutional structure, character and the party system, character and style in public policy.